Case reportAbscess of cauda equina presenting as lumboischialgic pain: a case report - Velnar, Tomaz; Bunc, Gorazd (Folia Neuropathologica, 2012)
Spinal intradural abscess is an uncommon form of pathology carrying poor prognosis, unless treated immediately. We report a case of a patient treated for intense lower back pain and neurological symptoms of foot paresis simulating a herniated lumbar disc. It was evident after image diagnostic procedure and surgery that an intradural abscess of cauda equina was the cause.